Perception of the parents of children with intestinal stoma regarding the nursing orientations (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: The present study aimed to identify the perception of the parents of children with intestinal elimination stoma about the guidelines received by the health team during hospitalization for their preparation. Methods: This is a cross-sectional, qualitative and quantitative study. Data collector occurred in the pediatric surgery ward of a university hospital through a semi-structured interview, recorded and composed of open and closed questions. Results: Nine parents of children with intestinal elimination stoma were followed up by the pediatric surgery team. Subsequently, it was submitted to the simple and categorical statistical analysis of Bardin. Regarding the main complications, the presence of dermatitis was indicated by 100% of the sample and the fungal infections followed by prolapse by 44.4%. The study showed that the lack of knowledge results in complications and insecurity. The support network is one of the resources used to search for information. A manual with guidelines was pointed out as a strategy for home care. Conclusion: Despite the failures in the guiding and supporting parents of children with a stoma, the feedbacks to help with changes and suggestions for valid strategies were important.